Characterization of Glycerol-Extractable Organic Matter from Etna Soils of Different Ages - BAGLIERI, A.; IOPPOLO, A.; NÈGRE, M.; ABBATE, C.; GENNARI, M. (Pedosphere, 2010)
We characterized humic acids （HAs） and glycerol-extractable organic fractions （GEOFs） extracted from four Andisols, taken from comparable soil-climate conditions on the east side of Mount Etna. The soils were formed on old lava （about 9000 years ago）, old tephra （about 8 700 years ago）, recent lava （about 2 600 years ago） and recent tephra （about 3600 years ago）. A part of the organic matter of the soils, deprived of HAs and fulvic acids （FAs）, was isolated by glycerol extraction. The GEOF can not be extracted with alkaline solutions, probably because it is closely bound to the mineral component of the soil. The characterization of the extracted organic fraction was carried out using elementary and functional group analysis and Fourier transform infrared （FT-IR） spectroscopy. About 20 extractions were necessary to extract the HA and FA from the older soils and about 10 extractions to extract them from the younger soils. Data showed that the CEOFs had a greater ash content and a smaller N content, as well as a greater presence of aliphatic compounds and carboxylic groups as compared to the HA extracted from the same soil. The GEOFs extracted from younger soils also had a lower yield, ash and COOH-group content, and were more aliphatic than the GEOF extracted from older soils. Finally, the GEOFs were more closely bound to the amorphous component of the soil （＇short-range＇ minerals） and consequently less subject to biodegradation.